(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Reactive arthritis (RеА) is a "sterile" inflammatory joint disease in which infectious agents and their antigens are absent in the synovial fluid and synovial membrane of patients. RеА is a seronegative spondyloarthritis, which meets the criteria of the European Group for the Study of Spondyloarthritis. With the introduction into clinical practice in the early 90s of the reverse transcriptase polymerase chain reaction (RT–PCR) method, small amounts of Ch.trachomatis DNA and RNA were found in the joint cavity. The presence of these nucleic acids, which have a very short lifetime in tissues (several minutes), indicated the possibility of transcription and, consequently, active reproduction of bacteria in the joint cavity.